Penguatan Pendidikan Agama Islam pada Madrasah Aliyah di Kudus - Ihsan, Ihsan (Nadwa, 2012)
Madrasah as an educational institution even stronger existence. Existing regula-tion has delivered madrassas in equal position and equal even the same as pub-lic schools. This condition exposes madrasas on the challenges and dilemmas that are difficult, especially when associated with objective conditions. General impact of the new status, decreased ability / mastery religious madrassa gradu-ates. This is caused by the demands of teaching general science which is equiva-lent to public schools in addition to teach theology. But it must be admitted, madrasa is an alternative education model because it has a plus compared to schools, namely Islamic religious education is sufficient.